Influence of different hardness custom foot insoles in the electromyography activity patterns of the thigh and hip muscles during motorcycling sport: a crossover study - Casado-Hernández, I.; Becerro-de-Bengoa-Vallejo, R.; Losa-Iglesias, M. E.; Martínez-Jiménez, E. M.; López-López, D.; Mazoteras-Pardo, V.; Romero-Morales, C.; Calvo-Lobo, C. (Sensors, 2020)
Nowadays, the use of insoles in sport practice have been recognized to decrease the foot and lower limb injury patterns. The aim of this study was to analyse the effect of four types of hardness insoles (HI) in the activity patterns of the hip and thigh muscles (HTM) in motoriders during motorcycling sport. The study was a crossover trial. Subjects were elite motoriders. The mean age was 33 ± 5.14 years. Electromyography (EMG) of hip and thigh muscles (HTM) data was registered via surface while subjects were riding on an elite motorcycle simulator. Subjects had to complete different tests with randomly hardest insoles (HI): 1: only polypropylene (58° D Shore); 2: Polypropylene (58° D Shore) with selective aluminium in hallux and metatarsal heads (60 HB Brinell hardness); 3: Ethylene vinyl acetate (EVA) (52° A Shore); and finally, 4: Ordinary EVA (25° A Shore) as the control. EMG patterns of the HTM, riding on an elite motorcycle simulator, showed the lowest peak amplitude with the insoles with polypropylene and selective aluminium. Using the hardest insoles in our study (selective aluminium) the EMG amplitude peaks decreased in all HTM.